MENINGKATKAN KREATIVITAS JIWA ANAK MELALUI PEMBUATAN KERAJINAN YANG BERMANFAAT UNTUK MENINGKATKAN KETERAMPILAN - Angelina Yulisa Makatuuk; Lihard Stevanus Lumampow; Yolitha Asera Pata'dungan; Putri Sabina Ragho; Sofia angela Runtu; Vabio putra Ngion; Lineke Angelika Goni (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: Based on the National Education System Law, the goals of education as explained in the law above mean that children living in orphanages have the same rights as children in general in the field of education. One of children's rights, apart from receiving formal education, is that they also have the right to receive support in developing their potential. The form of service is teaching how to make flowers and pencil cases from used materials. The aim of this activity is to train children's skills such as sharpening fine motor skills, patience, accuracy and social attitudes for interacting with other people. The research method employed includes lectures, demonstrations, and question and answer sessions. The outcome of this activity is the children's ability to create simple handicraft products using recycled materials such as plastic bottles. It is hoped that this activity will be continued by the children and will spark motivation in developing their creativity and entrepreneurial spirit.Keywords: Children; Handycrafts; Devotion; Training